Explorations in the Stone-Campbell traditions : essays in honor of Herman A. Norton - Norton, Herman Albert; Dunnavant, Anthony L., 1954-; Harrison, Richard L., Jr., 1946- (Published for the Disciples Divinity House at Vanderbilt University by the Disciples of Christ Historical Society, 1995)
This important collection of essays honors Herman A. Norton (1921-2002), Dean of the Disciples Divinity House at Vanderbilt University from 1951 until his retirement in 1986. Topics from all three branches of the Stone-Campbell Movement are treated including early leaders like Barton Stone and Alexander Campbell, as well as later studies after the Civil War and into the early 1940s.